Distribution of ِHuman Leptospirosis in Guilan Province, Northern Iran - H Honarmand; S Eshraghi; MR Khorramizadeh; RA Hartskeerl; FM Ghanaei; GR Abdolahpour; MR Eshraghian (Tehran University of Medical Sciences, 2007)
Background: Leptospirosis is the most widespread zoonosis in the world and is more prevalent in tropical and temperate regions. Guilan Province in north of Iran, is an endemic region of human leptospirosis. Since diagnosis of leptospirosis according to clinical symptoms is very difficult due to lack of characteristic pathogonomic sign(s), laboratory support is necessary. Methods: In 2003, we obtained blood samples from patients hospitalized in main general hospitals of Guilan Province and were suspected as having leptospirosis according to their clinical presentations. We examined 995 sera by a commercial IgM and IgG ELISA kit to find positive cases. Results: 62.7% of positive cases were male and about 86% of them were farmer. High distribution rate of leptospirosis was seen in middle-aged people (65% in 20-50 years old). Conclusion: It seems that leptospirosis has a high occurrence in major cities and is mostly distributed in warm months of the year. Demographic analysis of the results indicates that leptospirosis is typically a rural and an occupational disease in the area.